2017
DOI: 10.3126/kumj.v13i4.16838
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effectiveness of Ipsilateral Transversus Abdominis Plane Block in Adult Patients Undergoing Appendectomy: A Prospective Randomized Controlled Trial

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…To date, three randomized trials have investigated the benefits of transversus abdominis plane blocks for open appendectomy [195][196][197] and three studies have done the same for laparoscopic appendectomy. [198][199][200] Overall the findings have been fairly consistent.…”
Section: Appendectomymentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three randomized trials have investigated the benefits of transversus abdominis plane blocks for open appendectomy [195][196][197] and three studies have done the same for laparoscopic appendectomy. [198][199][200] Overall the findings have been fairly consistent.…”
Section: Appendectomymentioning
confidence: 99%
“…[198][199][200] Overall the findings have been fairly consistent. For open appendectomy, both lateral and posterior transversus abdominis plane blocks have been shown to result in decreased postoperative pain scores at rest and on movement as well as significant reductions in consumption of intravenous morphine (22 mg) and tramadol (78 mg) at 24 h and intravenous morphine (12.3 mg) at 48 h [195][196][197] despite the use of acetaminophen and diclofenac. 195,196 In contrast, for laparoscopic appendectomy, two trials have concluded that lateral transversus abdominis plane blocks provide no benefit in the setting of multimodal analgesia.…”
Section: Appendectomymentioning
confidence: 99%
“…There was no study investigating TAP blocks in adults for open appendicectomy. Ghimire and colleagues’ three-arm study examined the effect of morphine added to bupivacaine (either as an adjuvant in the TAP block or as intravenous morphine) 70 . Even though there was a significantly longer mean duration of analgesia measured by the time to first analgesic request in the group receiving morphine as an adjuvant, there was no significant reduction in pain intensity or opioid consumption.…”
Section: Regional Analgesia Techniquesmentioning
confidence: 99%
“…7 It provides effective analgesia for patients undergoing lower and upper abdominal surgeries such as cesarean delivery, open appendectomy, and liver resection. [8][9][10] However, no reports have described the postoperative analgesic effect of the TAP block on patients with hepatic echinococcosis (HE). Enhanced recovery after surgery (ERAS) is a comprehensive perioperative approach that aims to accelerate recovery after surgery.…”
Section: Introductionmentioning
confidence: 99%